Legalitas Pelayanan Perizinan Berbasis Online di Provinsi Sulawesi Tengah - Jauhari, Muhamad; Surahman, Surahman; Awaluddin, Awaluddin; Baco, Syamsuddin; Lasatu, Asri (Bomba: Jurnal Pembangunan Daerah, 2025)
The enactment of Government Regulation (GR) No. 28 of 2025th on Risk-Based Business Licensing has not been automatically followed by regulatory adjustments at the regional level nor by improvements to the electronically integrated licensing system (Online Single Submission). This condition has legal implications for the validity of business licenses and has hindered the delivery of licensing services administered by the Investment and One-Stop Integrated Services Office (DPMPTSP) of Central Sulawesi Province. This research aims to examine the extent of the juridical implications of the implementation of The enactment of Government Regulation on the legitimacy and authority of the Head of DPMPTSP in administering licensing services in Central Sulawesi. This study employs normative legal research, using a statutory approach, and a conceptual approach, which are analyzed and presented prescriptively. The findings indicate that the enactment of GR No. 28 of 2025 does not affect the institutional authority of the Head of DPMPTSP; however, its substantive authority related to types of licenses, including licensing norms, standards, procedures, and criteria, requires adjustments to the Governor’s Regulation in conformity with GR No. 28 of 2025 in order to ensure legal legitimacy.